2014
DOI: 10.1103/physrevlett.113.073001
|View full text |Cite
|
Sign up to set email alerts
|

Electron Rearrangement Dynamics in DissociatingI2n+Molecules Accessed by Extreme Ultraviolet Pump-Probe Experiments

Abstract: The charge rearrangement in dissociating I n+ 2 molecules is measured as a function of the internuclear distance R using XUV pulses delivered by the free-electron laser (FEL) in Hamburg. Within an XUV pump-probe scheme the first pulse initiates dissociation by multiply ionizing I 2 , and the delayed probe pulse further ionizes one of the two fragments at a given time, thus triggering charge rearrangement at a well-defined R. The electron transfer between the fragments is monitored by analyzing the delay-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Specifically, a core ionization that is purely located on one atomic site may give rise to charging up at another atomic site of the molecule, so the charges are redistributed among neighboring atoms within the molecule. This charge rearrangement might yield different ion fragments than one would expect from the x-ray ionization of the individual constituent atoms [20,22,23]. Theoretical descriptions for these observations have been developed so far only based on phenomenological models [19,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a core ionization that is purely located on one atomic site may give rise to charging up at another atomic site of the molecule, so the charges are redistributed among neighboring atoms within the molecule. This charge rearrangement might yield different ion fragments than one would expect from the x-ray ionization of the individual constituent atoms [20,22,23]. Theoretical descriptions for these observations have been developed so far only based on phenomenological models [19,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In this context electronic transition rates, i.e., photoionization cross sections and decay rates, were derived from the values for individual atoms. However, it has been found that relevant aspects of the radiation damage in molecules must be understood rather from the molecular electronic structure [7,[19][20][21][22][23]. Specifically, a core ionization that is purely located on one atomic site may give rise to charging up at another atomic site of the molecule, so the charges are redistributed among neighboring atoms within the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…These versatile x-ray sources will therefore soon open the pathway for implementing all x-ray pump-probe schemes. One very successful scheme turns out to be splitting of the FEL pulse into two replicas and using them as time-delayed pump and probe pulses; this scheme has been successfully applied to study interatomic Coulombic decay in neon dimers [11], charge transfer in iodine molecules [12] and iodomethane [13], photoexcited molecular dynamics [14] and so on; an even more elaborated scheme, which makes use of a pair of x-ray pulses with slightly different wavelengths [15][16][17][18][19], was used to probe ultrafast electronic and molecular dynamics [19][20][21][22][23]. Here, we propose a different x-ray pump-probe scheme based on two time-delayed x-ray pulses of different frequencies [15][16][17][18] to study vibrational wave-packet dynamics in core-excited electronic states.…”
Section: Introductionmentioning
confidence: 99%
“…However, extracting information from the experimental schemes involving strong-field interactions requires theoretical modeling to account for the induced strong-field effects [14]. With the advent of FELs, a new generation of pump-probe schemes was conceived that uses two XUV pulses [15][16][17][18]. The high flux of photons in a femtosecond pulse generated by FELs is crucial to obtain the needed signal in the pump-probe scheme, in which absorption of at least one photon from each pulse by the same molecule is required.…”
Section: Introductionmentioning
confidence: 99%